Resiliência familiar: imigração sírio-libanesa estratégias de enfrentamento para adaptação - Pacheco, Vera Terezinha Maluly (2016)
This work was developed focusing on the resilience process in the context of the Syrian-Lebanese immigration in the environment of Sao Paulo city. Immigration is a social and cultural phenomenon variable in time and space. The interference of immigration in the geographical area of destination and the interrelationships from this fact were studied. The dissertation was based on the systematic review of literature on resilience and Syrian-Lebanese immigration. In addition, two families of Syrian-Lebanese immigrants (first and second generation), residents of Sao Paulo city, have participated to the study, by means of interviews carried out with them. It was used the History of Life methodology. With the help of the memory of interviewers, this procedure allows to build up versions of the past and of their stories. These narratives have greatly contributed to the research process, which has been enriched with the presentation of photos and documents during interviews. The reports of these immigrants regarding their experience in another country have demonstrated that the adaptation process took place in a positive enriching way, but at the same time with difficulties. These reports also pointed out that the family support network and cultural structure in which they live in helped them to make the process of inclusion. The process of resilience developed by these immigrants enabled the transformation of people, awakening up their potential and enabling them to resume the meaning of life. The research involved the rescue of life stories through open interviews and photographs